PARAMETRIC ANALYSIS ON REFLECTOR DESIGNS OF SINGLE ELEMENT CYLINDRICAL DIELECTRIC RESONATOR ANTENNA (CDRA) FOR WLAN APPLICATIONS - ALI, SYED MUZAMMIL (2015)
In microwave communication field, reflector antennas are widely used in high gain wireless communication systems. The main constrain in reflector antenna design is the design of an efficient feed. Moreover, various techniques developed to enhance the gain ofsingle element DRA have limitations such as high cost, design complexity and fabrication impediments. Therefore, in this research work, the gain of single element DRA is enhanced by using DRA as a feed for three reflectors. The types of reflector explored are; flat, box shaped and parabolic reflector. The reflectors are implemented at the back ofthe CDRA design to reflect the backward radiation and consequently improving the forward gain of the antenna. The effect of reflectors on the resonant frequency, impedance bandwidth, directivity gain and backlobe leveliof CDRA are analyzed by using CST 3D Microwave Studio software.